Perceived teacher autonomy support for adolescents’ reading achievement: The mediation roles of control-value appraisals and emotions - Wang, Meishu; Hu, Jie (Frontiers in Psychology, 2022)
Analyzing students’ internal cognitive-motivational appraisals and achievement emotions is of pivotal importance for educational outcomes and student individual well-being, yet little is shown about their associations with teacher autonomy support. This study investigates the relationship between perceived teacher autonomy support and reading achievement by addressing mediating influences of control and value-related constructs, i.e., reading self-efficacy, meaning in life and reading enjoyment. Multiple mediation modeling was adopted to test the proposed model with carrying out a total of 12,058 students from 361 schools in China in the Programme for International Student Assessment (PISA) 2018 reading database. The results elucidated that student-perceived teacher autonomy support is significantly positively related to adolescents’ reading outcomes by fostering internal control and value appraisals and academic enjoyment. These current findings confirm the positive correlation between teacher autonomy support and adolescents’ motivational and emotional factors, providing significant practical implications for educators to adopt various teaching strategies to enhance adolescents’ self-efficacy, intrinsic values and positive emotions.